Timing of allergen exposure and the development of food allergy: treating before the horse is out of the barn. Issue 2 (April 2016) - Elizur, Arnon; Katz, Yitzhak
Abstract : Purpose of review: Until recently, nutritional guidelines did not support early introduction of allergenic foods into the diet of high-risk infants. Following recent studies, this approach is beginning to change, at least for peanuts. This review will examine the change in nutritional guidelines and the scientific data that led to these changes. Recent finding: In a recent prospective controlled study, regular consumption of peanut protein in infants from 4–11 months of age with atopic dermatitis or egg allergy, was associated with lower prevalence of peanut allergy (1.9%) at 60 months of age compared with peanut avoidance (13.7%). Other studies demonstrated that earlier introduction of cow's milk protein and egg powder were also associated with decreased risk for milk and egg allergy, respectively. Summary: Recent studies suggest that early rather than late introduction of allergenic foods reduces the risk of food allergy. The preferred timing of food introduction might be sooner than the current recommendation, and might apply not only to high-risk infants.